Thermodynamic Feasibility of Hydrogen-Rich Gas Production Supported by Iron Based Chemical Looping Process - Grzegorz Słowiński; Adam Smoliński (Journal of Chemistry)
The continuously increasing oil prices as well as stronger environmental regulations regarding greenhouse emissions made the greatest economic powers search a new, price competitive, and environment friendly energy carrier, such as hydrogen. The world research activities in these terms focus on the development of integrated hydrogen and power generating technologies, particularly technologies of hydrogen production from various carbonaceous resources, like methane, coal, biomass, or waste, often combined with carbon dioxide capture. In the paper the thermodynamic analysis of the enhancement of hydrogen production in iron based chemical looping process is presented. In this method, iron oxide is first reduced to iron with a reducing agent, such as carbon oxide, hydrogen, or mixture of both gases (synthesis gas), and then, in the inverse reaction with steam, it is regenerated to iron oxide, and pure stream of hydrogen is produced.